2022
DOI: 10.1080/21655979.2022.2044261
|View full text |Cite
|
Sign up to set email alerts
|

Methyltransferase-like 3 induces the development of cervical cancer by enhancing insulin-like growth factor 2 mRNA-binding proteins 3-mediated apoptotic chromatin condensation inducer 1 mRNA stability

Abstract: N6-methyladenosine (m6A) plays a critical role in the tumorigenesis of cervical cancer (CC). Here, we aimed to investigate the potential role of methyltransferase-like 3 (METTL3) in CC. Gene expression was determined via real-time quantitative polymerase chain reaction. Cellular functions were detected using colony formation, 5-ethynyl-2′-deoxyuridine (EdU), and Transwell assays. The interactions among METTL3, insulin-like growth factor 2 mRNA-binding protein 3 (IGF2BP3), and apoptotic chromatin condensation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…In colon cancer, IGF2BP3 boosts DNA replication and cell proliferation by binding to m 6 A-modified sites in CCND1 mRNA and preventing its degradation [ 56 ]. ACIN1 is stabilized through METTL3/IGF2BP3, boosting proliferation and migration of cervical cancer cells [ 57 ]. In hepatocellular carcinoma, lnc-CTHCC, stabilized by METTL3/IGF2BP1/IGF2BP3 via m 6 A modification, promotes tumor initiation and development by binding hnRNPK and activating YAP1 transcription [ 58 ].…”
Section: Introductionmentioning
confidence: 99%
“…In colon cancer, IGF2BP3 boosts DNA replication and cell proliferation by binding to m 6 A-modified sites in CCND1 mRNA and preventing its degradation [ 56 ]. ACIN1 is stabilized through METTL3/IGF2BP3, boosting proliferation and migration of cervical cancer cells [ 57 ]. In hepatocellular carcinoma, lnc-CTHCC, stabilized by METTL3/IGF2BP1/IGF2BP3 via m 6 A modification, promotes tumor initiation and development by binding hnRNPK and activating YAP1 transcription [ 58 ].…”
Section: Introductionmentioning
confidence: 99%
“…METTL3 could promote the occurrence and development of CC through IGF2BP3. 29 Additionally, METTL3 promotes CC progression by inhibiting endoplasmic reticulum stress through the m 6 A modification of TXNDC5 mRNA. 30 However, the specific mechanism of m 6 A action in CC remains unknown, given the diverse range of its functions.…”
Section: Mettl3 Regulates Pde3a Mrna Stability Through Ythdf3mentioning
confidence: 99%
“…Its overexpression inhibits the proliferation and migration ability of CC cells and enhances the apoptosis rate ( Ji et al, 2021 ). In addition, Mettl3 synergizes with IGF2BP3 to extend the half-life of ACIN1 and RAB2B mRNA to contribute to the growth of CC and poor prognosis ( Hu et al, 2020 ; Su et al, 2022 ). Recent research has revealed that Mettl3 is highly expressed in CC cells in the M stage, increases m6A methylation of CDC25B mRNA, and enhances its translation activity by recruiting YTHDF-1.…”
Section: The Role Of Mettl3 In Cervical Cancermentioning
confidence: 99%